ANALISIS DAMPAK PERUBAHAN KURIKULUM TERHADAP EFEKTIVITAS PEMBELAJARAN JENJANG PENDIDIKAN DASAR DAN MENENGAH - Hidayat, Rahmad; Bedi, Fisman; Fitri, Tin Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Curriculum change is an educational strategy designed to address the evolving demands of modern society and student needs. This study aims to examine the impact of curriculum changes on the effectiveness of learning at the primary and secondary education levels. A systematic literature review was conducted by analyzing empirical studies published between 2020 and 2024. Key variables examined include student academic achievement, motivation, teacher readiness, and infrastructure support. Findings indicate that curriculum changes positively influence learning effectiveness when supported by adequate teacher training and flexible curriculum implementation. The study highlights the significance of project-based learning and digital integration in enhancing student engagement and skills acquisition. These findings provide a comprehensive perspective for policymakers to design curricula that not only respond to global challenges but also enhance student learning outcomes effectively.